Intraoperative Cell Salvage as an Alternative to Allogeneic (Donated) Blood Transfusion: A Prospective Observational Evaluation of the Immune Response Profile - Michelle Roets; David John Sturgess; Maheshi Prabodani Obeysekera; Thu Vinh Tran; Kerstin Hildegard Wyssusek; Jaisil Eldo Jos Punnasseril; Diana da Silva; Andre van Zundert; Alexis Jacqueline Perros; John Paul Tung; Robert Lewis Powell Flower; Melinda Margaret Dean (Cell Transplantation, 2020)
Allogeneic blood transfusion (ABT) is associated with transfusion-related immune modulation (TRIM) and subsequent poorer patient outcomes including perioperative infection, multiple organ failure, and mortality. The precise mechanism(s) underlying TRIM remain largely unknown. During intraoperative cell salvage (ICS) a patient’s own (autologous) blood is collected, anticoagulated, processed, and reinfused. One impediment to understanding the influence of the immune system on transfusion-related adverse outcomes has been the inability to characterize immune profile changes induced by blood transfusion, including ICS. Dendritic cells and monocytes play a central role in regulation of immune responses, and dysfunction may contribute to adverse outcomes. During a prospective observational study ( n = 19), an in vitro model was used to assess dendritic cell and monocyte immune responses and the overall immune response following ABT or ICS exposure. Exposure to both ABT and ICS suppressed dendritic cell and monocyte function. This suppression was, however, significantly less marked following ICS. ICS presented an improved immune competence. This assessment of immune competence through the study of intracellular cytokine production, co-stimulatory and adhesion molecules expressed on dendritic cells and monocytes, and modulation of the overall leukocyte response may predict a reduction of adverse outcomes ( i.e., infection) following ICS.